Cross National Comparisons of Levels and Trends in Inequality - Peter Thomas Gottschalk; Timothy Michael Smeeding (Luxembourg Income Study (LIS), 1995)
This article builds on other reviews of changes in earnings inequality in the U.S. in tow important directions. First, the review is expanded to include other major industrialized countries, and second, the focus is broadened from earnings to household income. The general finding is that the U.S. experience of increases in the dispersion of both individual earnings and total household income is not unique, but only the U.K. experienced as large or larger increases in inequality during the 1980's. While most countries experienced at least modest increases in earning and market income inequality, these were largely offset by changes in other sources of income, producing a more modest increase in the inequality of disposable income and even lesser changes in poverty in most nations.
Keywords: 330; Einkommensverteilung; Haushaltseinkommen; Industrieländer